Phosphorylation of OmpR by the osmosensor EnvZ modulates expression of the ompF and ompC genes in Escherichia coli. - Forst, S (1989)
EnvZ and OmpR, the regulatory proteins for ompF and ompC expression in Escherichia coli, belong to a modulator-effector family of regulatory proteins which are essential for the response to environmental signals. We show that the soluble cytoplasmic domain of the transmembrane modulator protein EnvZ is phosphorylated in vitro by [gamma-32P]-ATP. We also demonstrate that the phosphate group can, in turn, be transferred to the transcription activator protein OmpR. The pH stability properties of the phosphate groups linked to EnvZ indicate that this molecule contains histidyl phosphate. The invariant His-243 of EnvZ corresponds to the phosphorylated His-48 of the chemotactic modulator protein CheA. Substitution of His-243 with valine produces an EnvZ that is refractory to phosphorylation and can no longer catalyze the transfer of phosphate to OmpR. Furthermore, in a delta envZ strain of E. coli, containing the envZ Val-243 plasmid, ompC expression is elevated 7-fold relative to that found in cells carrying the wild-type envZ plasmid. Based on these results we propose a model in which the phosphorylated state of OmpR modulates the expression of the ompF and ompC genes.